Governance revisited : challenges and opportunities for vocational education and training - Bürgi, Regula [Herausgeber]; Gonon, Philipp [Herausgeber] (Peter Lang, 2021)
"Global trends, such as an ever-rising service economy, rapid technological change and digitalization, challenge skill formation systems. Focussing on European countries, this edited volume examines the variety of European VET governance and VET governance research. In particular, it provides insights into regional, local and decentralized governance at meso (e.g. professional associations) as well as micro level (e.g. learning arrangements). As such, the edited volume sheds light on the hitherto far less explored dimensions of VET governance and highlights challenges as well as opportunities in VET governance in the 21st century." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S System beruflicher Bildung; S 4.3 Steuerung; I 2.2 Europa; 370; Berufsbildungspolitik; Berufsbildungssystem; Governance; Berufsverband; Lernarrangement; Kompetenzentwicklung; Europa; Deutschland; Dänemark; England; Finnland; Italien; Japan; Norwegen; Schottland; Schweiz; Österreich